Incidence of hematologic malignancy and cause‐specific mortality in the Women's Health Initiative randomized controlled trial of calcium and vitamin D supplementation. Issue 21 (27th June 2017) - Ammann, Eric M.; Drake, Matthew T.; Haraldsson, Bjarni; Wallace, Robert B.; Johnson, Karen C.; Desai, Pinkal; Lin, Emily M.; Link, Brian K.
Abstract : BACKGROUND: Prior evidence of a possible link between vitamin D status and hematologic malignancy (HM) in humans comes from observational studies, leaving unresolved the question of whether a true causal relationship exists. METHODS: The authors performed a secondary analysis of data from the Women's Health Initiative Calcium/Vitamin D (CaD) trial, a large randomized controlled trial of CaD supplementation compared with placebo in older women. Kaplan‐Meier and Cox proportional hazards survival analysis methods were used to evaluate the relationship between treatment assignment and 1) incident HM and 2) HM‐specific mortality over 10 years following randomization. HMs were classified by cell type (lymphoid, myeloid, or plasma cell) and analyzed as distinct endpoints in secondary analyses. RESULTS: A total of 34, 763 Women's Health Initiative CaD trial participants (median age, 63 years) had complete baseline covariate data and were eligible for analysis. Women assigned to CaD supplementation had a significantly lower risk of incident HM (hazard ratio [HR], 0.80; 95% confidence interval [95% CI], 0.65‐0.99) but not HM‐specific mortality (HR, 0.77 [95% CI, 0.53‐1.11] for the entire cohort; and HR, 1.03 [95% CI, 0.70‐1.51] among incident HM cases after diagnosis). In secondary analyses, protective associations were found to be most robust for lymphoid malignancies, with HRs of 0.77 (95% CI, 0.59‐1.01) and 0.46 (95% CI, 0.24‐0.89), respectively, for cancer incidence and mortality in those assigned to CaD supplementation. CONCLUSIONS: The current post hoc analysis of data from a large and well‐executed randomized controlled trial demonstrates a protective association between modest CaD supplementation and HM risk in older women. Additional research concerning the relationship between vitamin D and HM is warranted. Cancer 2017;123:4168–4177. © 2017 American Cancer Society . Abstract : In the Women's Health Initiative Calcium/Vitamin D trial, women assigned to calcium and vitamin D appear to have a significantly lower risk of incident hematologic malignancies over 10 years of follow‐up. Although no significant association with hematologic cancer‐specific mortality is noted, further research is needed to elucidate the possible role of vitamin D (and/or calcium) in the development and progression of hematologic malignancies.